Skeletal rearrangement of 6,8-dioxabicyclo[3.2.1]octan-4-ols promoted by thionyl chloride or Appel conditions - Jevric, Martyn; Klepp, Julian; Puschnig, Johannes; Lamb, Oscar; Sumby, Christopher J.; Greatrex, Ben W. (Beilstein Journal of Organic Chemistry, 2024)
A skeletal rearrangement of a series of 6,8-dioxabicyclo[3.2.1]octan-4-ols has been developed using SOCl2 in the presence of pyridine. An oxygen migration from C5 to C4 was observed when the C4 alcohols were treated with SOCl2/pyridine, giving a 2-chloro-3,8-dioxabicyclo[3.2.1]octane ring-system via the chlorosulfite intermediate. Analogous allylic alcohols with endocyclic and exocyclic unsaturations underwent chlorination without rearrangement due to formation of allylic cations. The rearrangement was also demonstrated using Appel conditions, which gave similar results via the alkoxytriphenylphosphonium intermediate. Several reactions of the products were investigated to show the utility of the rearrangement.
Keywords: bicyclic ring; cyrene; levoglucosenone; rearrangement; thionyl chloride